MODELING DOMESTIC TOURISM DEMAND IN GALICIA USING THE ARDL APPROACH - MANUEL GONZÁLEZ-GÓMEZ; MARCOS ÁLVAREZ-DÍAZ; MARISOL OTERO-GIRÁLDEZ PhD, Department of Applied Economics, University (Tourism & Management Studies)
Tourism is one of the most important sectors for the economy of Galicia (North-west of Spain). The aim of our study is to find the most important socio-economic factors that statistically influence the domestic tourism demand for Galicia. For this purpose, we make use of the ARDL bounds testing cointegration approach (Pesaran et al., 2001). Once the main influencing factors are known, we construct an econometric model using a general-tospecific ARDL modeling procedure. The estimated coefficients of the model allow us to quantify the impact of the influencing factors on the Galician domestic tourism demand. According to our results, the income elasticity of demand tends to be unitary; that is, an increase of 1 per cent in the income of Spanish residents produces a rise of around 1 per cent in the domestic tourism demand. Moreover, the Eastern vacations and the celebration of the Holy Year increase the tourism demand by around 11 per cent. Finally, the economic crisis and the differential of inflation between Galicia and the rest of Spain decrease the tourism demand in a 7.5 per cent.